2004
DOI: 10.1002/em.20056
|View full text |Cite
|
Sign up to set email alerts
|

Role of DNA mismatch repair in apoptotic responses to therapeutic agents

Abstract: Deficiencies in DNA mismatch repair (MMR) have been found in both hereditary cancer (i.e., hereditary nonpolyposis colorectal cancer) and sporadic cancers of various tissues. In addition to its primary roles in the correction of DNA replication errors and suppression of recombination, research in the last 10 years has shown that MMR is involved in many other processes, such as interaction with other DNA repair pathways, cell cycle checkpoint regulation, and apoptosis. Indeed, a cell's MMR status can influence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
48
1
1

Year Published

2005
2005
2012
2012

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 53 publications
(52 citation statements)
references
References 167 publications
(195 reference statements)
2
48
1
1
Order By: Relevance
“…(reviewed in refs. [34][35][36][37]. Induction of p21 waf1/cip1 is also implicated in a G 2 -M arrest in both p53-proficient (38) and p53-deficient (31,39,40) cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…(reviewed in refs. [34][35][36][37]. Induction of p21 waf1/cip1 is also implicated in a G 2 -M arrest in both p53-proficient (38) and p53-deficient (31,39,40) cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…The MMR system has been implicated in cell killing by fluoropyrimidines (FPs) as MMRdeficient cells exhibit increased survival after treatment with FdU (Meyers et al, 2004). Arrest in G2 is observed within the first cell cycle in MMR-proficient cells, but not in MMR-deficient cells (Carethers et al, 1999;Meyers et al, 2003Meyers et al, , 2005.…”
Section: Mmr and Dna Damage Signallingmentioning
confidence: 99%
“…For example, Pani et al (2007) have shown that the MMR pathway contributes to the cytoxicity of cisplatin in human cells; however, other pathways are also critical in mediating the response to cisplatin particularly homologous recombination. In the case of FdU, widely used as an adjuvant therapy in advanced colorectal cancer, MMR-mediated apoptosis (Meyers et al, 2005) may be one of several contributors to the overall cytotoxicity of FdU as base excision repair (BER) enzymes also target FdU (Meyers et al, 2004). The BER enzyme SMUG1 removes FdU from DNA and confers protection from cell killing .…”
Section: Mmr and Dna Damage Signallingmentioning
confidence: 99%
“…Additionally, in hereditary nonpolyposis colon cancer patients, germ line missense mutations have been identified in MMR pathway members, including MLH1, MSH2, and MSH6 (4 -6). Aberrant or reduced levels of MMR can result in defects in apoptosis, leading to resistance to therapy (7,8).…”
mentioning
confidence: 99%